Immediate and controlled-release pregabalin for the treatment of epilepsy. (2nd December 2019) - Morano, Alessandra; Palleria, Caterina; Citraro, Rita; Nesci, Valentina; De Caro, Carmen; Giallonardo, Anna Teresa; De Sarro, Giovambattista; Russo, Emilio; Di Bonaventura, Carlo
ABSTRACT: Introduction : Epilepsy is a common neurological disease requiring complex therapies, which are unable to achieve seizure control in 30% of patients. Poor adherence has been recognized as a possible determinant of drug-resistance. Prolonged-release formulations of antiepileptic drugs might help increase adherence and minimize side effects. Areas covered : Pregabalin (PGB) has peculiar pharmacodynamics and almost ideal pharmacokinetics, except for a short half-life and therefore requiring multiple daily dosing. PGB immediate-release (IR) is effective in focal-onset epilepsy (FOE), neuropathic pain, generalized anxiety disorder, and fibromyalgia, despite some tolerability issues, especially at higher doses. The controlled-release formulation (CR) shares PGB IR advantages and requires slight dose adjustments to guarantee bioavailability. In 2014, PGB CR (165 and 330 mg/day) failed to prove superior to placebo in a randomized placebo-controlled trial on 323 subjects with drug-resistant FOE, although it was just as tolerable. Therefore, PGB CR is not currently licensed for epilepsy. Expert opinion : Considering the disappointing results of the only controlled trial, PGB CR is unlikely to become an established epilepsy treatment anytime soon. Nevertheless, given its peculiar properties and potential advantages, PGB (in either formulation) should be further evaluated in specific populations of patients, especially fragile subjects with several comorbidities and complex polytherapies.